ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI INDUSTRI KERAJINAN PATUNG KAYU DI KECAMATAN SUKAWATI - I Wayan Permana Adi Putra; Sudarsana Arka (E-Jurnal Ekonomi Pembangunan, 2023)
The development of the production value of the wooden sculpture industry in Sukawati Districthas fluctuated from 2017-2021. The purpose of this study was to analyze the economies ofscale and the factors that influence production in the wooden sculpture industry in SukawatiDistrict. The data used is primary data and the analysis technique used is multiple linearregression analysis with the Cobb-Douglas approach. The results showed that capital, laborand technology simultaneously affected the production of the wooden sculpture industry andpartially capital and labor had a positive and significant effect on the production of thewooden sculpture industry, while technology was a dummy variable stating that theproduction of wooden sculptures using Modern technology is higher than using traditionaltechnology and the wooden sculpture industry in Sukawati District. is in a condition ofIncreasing Return to Scale.